Effect of Different Activators on Rheological and Strength Properties of Fly Ash-Based Filling Cementitious Materials - Liu Fangfang; Feng Xiyang; Chen Li (Advances in Civil Engineering)
In this paper, lime, gypsum, NaOH, and Na2SO4 are mainly used to study the activation degree and activation mechanism of fly ash, and L9 (34) orthogonal table is used for the orthogonal test. The influence of different activators on the rheological and strength properties of slurry was analyzed. The microstructure and hydration products of fly ash cement cementitious body were studied by SEM and XRD. The results show that the bleeding rate of slurry containing activator fly ash system is between 2.24% and 3.37%, which is much higher than that of pure cement slurry (9.25%). Therefore, the addition of this system can improve the fluidity of slurry, and the optimal scheme is a3b2c2d2. The results show that the compressive strength of cement with activator fly ash system is much lower than that of pure cement, but the increase of strength is between 31% and 85%, which is much greater than that of pure cement (35%–46%). The optimal scheme is A2B2C3D3 or A3B2C3D3 at 3 days and A1B3C2D3 at 28 days. According to the scanning results of SEM and XRD, the addition of activator can significantly improve the hydration degree of fly ash and form a more complex network structure without obvious gap.